Overview of the Economic Importance of Foot and Mouth Disease on Milk Production in Dairy Cows - Habibi, Emal (Journal of Natural Sciences – Kabul University, 2020)
Foot and Mouth disease is one of the most damaging diseases in ruminant animals, causing major economic losses to livestock. Foot and Mouth disease is a highly contagious viral disease that affects ruminant animals such as cattle, sheep, goats, and pigs, with the most severe effects seen in cattle and pigs. It causes fever, vesicles, and ulcers in the mouth, legs, and udder of ruminant animals. The etiology of Foot and Mouth disease belongs to the family Picornaviridae and the genus Aphthovirus. The serotypes of the virus include A, O, C, SAT-1, SAT-2, SAT-3, and Asia-1. Foot and Mouth disease generally causes both direct and indirect economic losses. The disease significantly affects the animals' milk yield, reducing it by up to 63.40%.